Instrumen Investasi Syariah Sebagai Alat Alternatif Investasi Bodong di Era Industri 5.0 - angella20, jemima20; Oktafia, Renny (Journal of Economics and Business Aseanomics, 2023)
The growth of the financial industry in the industrial era 5.0 requires a creative mindset to face new opportunities or challenges as a result. One of the problems that arises is the existence of fraudulent investments that harm investors. Therefore, exploring sharia investment instruments that are used as safe alternative tools is used as a research objective in the midst of the rush of fraudulent investments. Through a literature review and in-depth description, sharia investment instruments such as sharia shares, sharia bonds or sukuk, sharia mutual funds, sharia savings, sharia deposits, gold and property will be assessed for their historical performance and strength. So that it can become a halal and trusted investment preference for the community. The research results prove that sharia investment instruments can not only be a good and long-lasting option in the industrial era 5.0, but also provide a solution to fraudulent investments in order to achieve financial goals with minimum risk.